2021
DOI: 10.1016/j.bbrc.2020.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity loss and COVID-19 pandemic: The role of bats in the origin and the spreading of the disease

Abstract: The loss of biodiversity in the ecosystems has created the general conditions that have favored and, in fact, made possible, the insurgence of the COVID-19 pandemic. A lot of factors have contributed to it: deforestation, changes in forest habitats, poorly regulated agricultural surfaces, mismanaged urban growth. They have altered the composition of wildlife communities, greatly increased the contacts of humans with wildlife, and altered niches that harbor pathogens, increasing their chances to come in contact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 155 publications
0
47
0
2
Order By: Relevance
“…However, subsequent extensive epidemiology studies had failed to find SARS-CoV in farmed and wild-caught civet cats, indicating that other animal(s) might have been the natural virus reservoir of SARS-CoV [ 26 , 27 ]. It was also found that strains of SARS-CoV isolated from palm civets in 2002–2003 and 2005, had low affinity for human ACE2 receptors and low infectivity in human cells, but had high affinity for civet cat ACE2 receptors and high infectivity in civet cat cells [ 25 ],Therefore, there is a strong possibility that these animals were only incidental hosts for the SARS-CoV [ 1 , 3 ]. In fact, no intermediate host has yet been established for SARS-CoV [ 28 ].…”
Section: The Spike-protein: Sars-cov and Sars-cov-2mentioning
confidence: 99%
See 4 more Smart Citations
“…However, subsequent extensive epidemiology studies had failed to find SARS-CoV in farmed and wild-caught civet cats, indicating that other animal(s) might have been the natural virus reservoir of SARS-CoV [ 26 , 27 ]. It was also found that strains of SARS-CoV isolated from palm civets in 2002–2003 and 2005, had low affinity for human ACE2 receptors and low infectivity in human cells, but had high affinity for civet cat ACE2 receptors and high infectivity in civet cat cells [ 25 ],Therefore, there is a strong possibility that these animals were only incidental hosts for the SARS-CoV [ 1 , 3 ]. In fact, no intermediate host has yet been established for SARS-CoV [ 28 ].…”
Section: The Spike-protein: Sars-cov and Sars-cov-2mentioning
confidence: 99%
“…Macaques are widely traded for consumption in South East Asia, and are frequently found in markets where they are kept together with other animals, including bats. Considering macaques’ close phylogenetic relationship to humans, the possibility of the transfer of SARS-CoV-2 from bats to them as intermediate hosts for the spillover to humans seems plausible [ 3 ].…”
Section: The Spike-protein: Sars-cov and Sars-cov-2mentioning
confidence: 99%
See 3 more Smart Citations